Fashioning Suburban Aspiration: Awheel with the Catford Cycling Club, 1886–1900. (November 2014) - Biddle-Perry, Geraldine
<x content-type="archive" xml:space="preserve">Abstract</x> This essay interrogates young men's participation in cycling club activities in suburban London in the last decades of the nineteenth century. The records of various London cycling clubs, but in particular those belonging to the Catford Cycling Club in South East London (extant), are used to examine the cycling 'boom' at the end of the nineteenth century in terms of a new geography of status display. The essay situates suburban club cycling in the context of a Victorian Rational Recreation Movement and as an example of the popular dissemination of its ideals. The essay explores how concepts of 'improvement', allied to greater access to new forms of leisure and fashionable consumption, served as a model of bourgeois conformity but also offered opportunities for the negotiation of new and more heterogeneous social identities.